2016
DOI: 10.4401/ag-7022
|View full text |Cite
|
Sign up to set email alerts
|

Historical and recent sea level rise and land subsidence in Marina di Ravenna, northern Italy

Abstract: The regions facing the northern Adriatic Sea are particularly vulnerable to sea-level rise. Several trade ports are located there, and the area is important from social and economical viewpoints. Since tourism and cultural heritage are a significant source of income, an increase in sea-level could hinder the development of these regions. One of the longest sea-level time series in the northern Adriatic, which goes back to the late 1880s, has been recorded at Marina di Ravenna, in Emilia-Romagna region. The rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…idliv ello= 1414) from 1992 to 2016 for sub-periods: 1992-2000, 2002-2006, 2006-2011, and 2011-2016. The subsidence data were acquired with topographic and Interferometric Synthetic Aperture Radar (InSAR) techniques calibrated on a 2005 topographic survey and a GPS permanent network (Cerenzia et al 2016;Teatini et al 2005). The data were elaborated with the QGIS software to obtain subsidence maps and isokinetics (mm/year) for the different sub-periods.…”
Section: Subsidence Datamentioning
confidence: 99%
See 2 more Smart Citations
“…idliv ello= 1414) from 1992 to 2016 for sub-periods: 1992-2000, 2002-2006, 2006-2011, and 2011-2016. The subsidence data were acquired with topographic and Interferometric Synthetic Aperture Radar (InSAR) techniques calibrated on a 2005 topographic survey and a GPS permanent network (Cerenzia et al 2016;Teatini et al 2005). The data were elaborated with the QGIS software to obtain subsidence maps and isokinetics (mm/year) for the different sub-periods.…”
Section: Subsidence Datamentioning
confidence: 99%
“…The San Vitale basin has been relatively stable in the past 15 years, as shown by the decline of drainage rate in this period. Cerenzia et al (2016) reported that Marina di Ravenna, a town in the San Vitale basin, is recently more stable and emphasized that the forthcoming sub-periods subsidence…”
Section: Subsidence Ratementioning
confidence: 99%
See 1 more Smart Citation